Analisis Kompetensi dan Pengalaman Kerja, Adakah Pengaruhnya Terhadap Kinerja ? - Serlina Ika Wulandari; Mutinda Teguh Widayanto; RR Setyani Hidayati (Ecobuss, 2020)
The purpose of this study is to analyze the level of competence and work experience and to determine whether there is an effect on performance. This study was conducted at PT Amak Firdaus Utomo. This research method is descriptive and causal associative and takes a sample of 45 respondents, the data collection method uses a questionnaire and the sampling technique uses saturated sampling. The analytical tool used is a questionnaire test consisting of validity and reliability tests, classical assumption tests, multiple regression tests, determination tests, hypothesis testing consisting of t test, F test and dominant test. The results showed that the level of competence and work experience were at a high degree, and it was found that both the competency and work experience had an effect on performance.